On the development of selective chelators for Cadmium: Synthesis, structure and chelating properties of 3-((5-(trifluoromethyl)-1,3,4-thiadiazol-2-yl)amino)benzo[d]isothiazole 1,1-dioxide, a novel Thiadiazolyl Saccharinate - Leal, Joana F. (2021)
Aquatic contamination by heavy metals is a major concern for the serious negative consequences it has for plants, animals, and humans. Among the most toxic metals, Cd(II) stands out since selective and truly efficient methodologies for its removal are not known. We report a novel multidentate chelating agent comprising the heterocycles thiadiazole and benzisothiazole. 3-((5-(trifluoromethyl)-1,3,4-thiadiazol-2-yl)amino)benzo[d]isothiazole 1,1-dioxide (AL14) was synthesized from cheap saccharin and characterized by different techniques, including single crystal X-ray crystallography. Our studies revealed the efficiency and selectivity of AL14 for the chelation of dissolved Cd(II) (as compared to Cu(II) and Fe(II)). Different spectral changes were observed upon the addition of Cd(II) and Cu(II) during UV-Vis titrations, suggesting different complexation interactions with both metals.